Hubungan antara Self Regulated Learning dan Self Compassion dengan Prokrastinasi Akademik pada Siswa - Hidayatur Rahmi Rifa’i; Isna Asyri Syahrina (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the relationship betweenthe regulated learning and self compassion with academic procrastination in class XI students at Solok MAN 2. The independent variable in this study is self regulated learning and self compassion and the dependent variable is academic procrastination. The measuring instrument used in this study is the scale of self regulated learning, the scale of self compassion and the scale of academic procrastination. The population in this study were 89 students of MAN 2 Solok. The sampling technique in this study used a saturated sampling technique. The sample in this study were 89 students of class XI at MAN 2 Solok. Validity and reliability test in this study using alpha cronbach technique. The results of the validity coefficient on the scale of self regulated learning moves from rix= 0.303 with the reliability coefficient of α = 0.905 while on thescale self compassion moves from rix= 0.494 with the reliability coefficient of α = 0.970 and on the moving academicprocrastination scale from rix= 0.324 with a reliability coefficient of α = 0.939. Based on the data analysis, the correlation between self-regulated learning and academic procrastination was obtained at -0,679 with a significance level of 0,000 and the correlation between self-compassion and academic procrastination was -0,524 with a significance level of 0,000 and the correlation between self regulated learning and selfcompassion together with Academic procrastination is 0.691 with a significance level of 0.000 which means the hypothesis is accepted. This shows that there is a significant relationship between self regulated learning and self compassion with academic procrastination in class XI students at MAN 2 Solok.